1992
DOI: 10.1017/s0317167100042232
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Management of Spinal Epidural Abscess

Abstract: ABSTRACT:Twenty-five patients with spinal epidural abscess were treated at the University of Western Ontario hospitals between July 1980 and July 1990. There were eighteen males (72%) and seven females (28%), with a median age of 60 years. Concurrent illness resulting in immunocompromise was present in 60%. Eleven presented with complete myelopathy, thirteen had limb weakness, and one had no neurological deficit. In twenty cases the abscess consisted of frankly purulent material, while in five the epidural col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0
2

Year Published

1994
1994
2007
2007

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 38 publications
1
48
0
2
Order By: Relevance
“…The lowest age was reported by Dei-Anang et al [80], who found a mean age of only 34 years in a group of 15 patients. Maslen et al [231] reported a mean of 67 years of age in a group of 28 patients with SEA, which represents the highest average age in all published case series [16,31,73,74,80,81,98,141,154,172,177,189,201,212,213,231,235,253,283,297,300,306,316,370,391,401]. However, Dei-Anang et al [80] included in their patient group four children aged 2 to 6 as well as five patients from 19 In this review, articles published between 1954 and 1997 concerning a total of 915 patients with SEA were statistically analyzed [1, 3-5, 11-14, 16, 17, 24, 31-33, 35-40, 43-46, 50, 55, 57-61, 63, 65, 66, 70, 71, 73, 74, 77, 79-81, 84-86, 89, 92-94, 96-100, 103-108, 110, 115-117, 121-124, 126-128, 133, 134, 137, 138, 141-143, 146-149, 152, 154, 156, 158, 160, 161, 166, 168, 170, 172, 176-178, 180-182, 184-189, 191, 193, 194, 198-202, 204, 206, 208, 211-217, 220, 222-227, 229, 231-233, 235, 237, 240-242, 244, 245, 250, 253, 254, 256, 259, 260, 264-266, 269-271, 273, 276-278, 280, 283, 293, 294, 297-300, 303-306, 308, 311, 315-318, 321, 324, 326-328, 330, 332, 335, 336, 339, 341-343, 345-348, 351, 352, 354, 357-359, 362, 365, 370, 372, 373, 379-385, 388, 390, 391, 395, 397-399, 401, 403].…”
Section: Epidemiologymentioning
confidence: 98%
See 4 more Smart Citations
“…The lowest age was reported by Dei-Anang et al [80], who found a mean age of only 34 years in a group of 15 patients. Maslen et al [231] reported a mean of 67 years of age in a group of 28 patients with SEA, which represents the highest average age in all published case series [16,31,73,74,80,81,98,141,154,172,177,189,201,212,213,231,235,253,283,297,300,306,316,370,391,401]. However, Dei-Anang et al [80] included in their patient group four children aged 2 to 6 as well as five patients from 19 In this review, articles published between 1954 and 1997 concerning a total of 915 patients with SEA were statistically analyzed [1, 3-5, 11-14, 16, 17, 24, 31-33, 35-40, 43-46, 50, 55, 57-61, 63, 65, 66, 70, 71, 73, 74, 77, 79-81, 84-86, 89, 92-94, 96-100, 103-108, 110, 115-117, 121-124, 126-128, 133, 134, 137, 138, 141-143, 146-149, 152, 154, 156, 158, 160, 161, 166, 168, 170, 172, 176-178, 180-182, 184-189, 191, 193, 194, 198-202, 204, 206, 208, 211-217, 220, 222-227, 229, 231-233, 235, 237, 240-242, 244, 245, 250, 253, 254, 256, 259, 260, 264-266, 269-271, 273, 276-278, 280, 283, 293, 294, 297-300, 303-306, 308, 311, 315-318, 321, 324, 326-328, 330, 332, 335, 336, 339, 341-343, 345-348, 351, 352, 354, 357-359, 362, 365, 370, 372, 373, 379-385, 388, 390, 391, 395, 397-399, 401, 403].…”
Section: Epidemiologymentioning
confidence: 98%
“…However, Dei-Anang et al [80] included in their patient group four children aged 2 to 6 as well as five patients from 19 In this review, articles published between 1954 and 1997 concerning a total of 915 patients with SEA were statistically analyzed [1, 3-5, 11-14, 16, 17, 24, 31-33, 35-40, 43-46, 50, 55, 57-61, 63, 65, 66, 70, 71, 73, 74, 77, 79-81, 84-86, 89, 92-94, 96-100, 103-108, 110, 115-117, 121-124, 126-128, 133, 134, 137, 138, 141-143, 146-149, 152, 154, 156, 158, 160, 161, 166, 168, 170, 172, 176-178, 180-182, 184-189, 191, 193, 194, 198-202, 204, 206, 208, 211-217, 220, 222-227, 229, 231-233, 235, 237, 240-242, 244, 245, 250, 253, 254, 256, 259, 260, 264-266, 269-271, 273, 276-278, 280, 283, 293, 294, 297-300, 303-306, 308, 311, 315-318, 321, 324, 326-328, 330, 332, 335, 336, 339, 341-343, 345-348, 351, 352, 354, 357-359, 362, 365, 370, 372, 373, 379-385, 388, 390, 391, 395, 397-399, 401, 403]. Some publications did not include detailed information on patient age [16,31,55,73,74,80,141,158,172,176,206,212,213,232,253,297,300,316,401]. Additionally, some only indicate the average age and the range of ages, without indicating the exact age of individual patients [16,31,73,74,80,141,158,172,177,212,213,232,…”
Section: Epidemiologymentioning
confidence: 99%
See 3 more Smart Citations